Shipboard Acoustic Doppler Current Profiler measurements during R/V Littorina cruise L10-22 - Barnapratim Sarma; Maike Paul (PANGAEA, 2024)
Vessel-mounted Acoustic Doppler Current Profiler (ADCP) measurements were carried out to acquire velocity profiles at two sites north (start: latitude & longitude: 54.229515,7.8437233) and northwest (start: latitude & longitude: 54.20431,7.862079) of Helgoland (Germany) during neap tide in June 2022 (29.06.2022 and 30.06.2022). The parallel transect method was adopted to acquire data over a semidiurnal tidal cycle that spanned 13 hours. On both days, surveys were conducted in a way where all the transects were traversed multiple times only from one direction. Each transect was ~1500 m and had a spacing of ~150 m. With a vessel speed of ~4 to 5 knots, each circuit formed by the 4 transect lines was traversed about ~13 times during the survey period of 13 hours. The measurements were conducted in bottom tracking mode with a 614.4-kHz Teledyne RD Instruments WorkHorse broadband ADCP. The ADCP was installed in convex and Janus configuration with a beam angle of 20 degrees to the supporting pole from the starboard side of the ship FK Littorina. The transducer face of the ADCP was 1.16 m below the water level, with a blank after transmitting (WF) set to 0.44 m. The ADCP was operated in a dynamic sea state (WM1) profiling mode with a depth cell length (WS) of 0.5 m and a total of 80 depth cells (WN). The bottom track pings per ensemble (BP) and pings per ensemble (WP) were set to 1; thus, 1 ensemble has 2 pings. The depth range covered by the ADCP is 2.10 m to 41.60 m. The data acquisition software ViSea DAS from Aqua Vision (https://aquavision.nl/services/visea-users/) used pitch and roll data from the ADCP extquotesingles internal built-in motion reference unit and navigation and heading data from an auxiliary unit onboard the research vessel on a serial RS-232 interface to convert ADCP velocities into earth coordinates. The navigational data received correction signals to receive RTK "fix" status during the survey period, and the ADCP offsets were determined before the surveys to ensure the thoroughness and reliability of the data collection process.